Multilocus sequence typing of clinical Burkholderia pseudomallei isolates from Cambodia. - Emmanuel Gyamfi; Gauthier Delvallez; Sokleaph Cheng; Soda Meng; Kimyeun Oeurn; Chanchakriya Sam; Alexandra Kerleguer; Bertrand Guillard; Anne-Laure Bañuls; Mallorie Hide (PLoS Neglected Tropical Diseases)
Melioidosis is a neglected tropical disease caused by Burkholderia pseudomallei, endemic to Southeast Asia and Northern Australia. Despite its increasing global public health and clinical significance, the molecular epidemiology of melioidosis and genetic diversity of B. pseudomallei in Cambodia remains poorly understood. This study aims to elucidate the genetic diversity and antibiotic susceptibility profiles of B. pseudomallei isolates responsible for melioidosis in humans. For this purpose, 14 clinical isolates cryopreserved at the Medical Biology Laboratory at Institut Pasteur du Cambodge from 2016 to 2020 were subjected to antimicrobial susceptibility testing and Multilocus Sequence Typing (MLST). Phenotypic testing revealed that 92.86% (13/14) of the isolates were sensitive to all tested antibiotics, while one isolate exhibited resistance to trimethoprim-sulfamethoxazole. MLST analysis resolved our isolates into 14 unique Sequence Types (STs), including 10 previously documented in Southeast Asia. Notably, ST1858, ST2064, ST2065, and ST2066 were identified as novel STs, while ST54, ST99, ST211, and ST1359 were reported in Cambodia for the first time in this study. Comparing our MLST data with available sequences on PubMLST (n = 165), our study unveiled a high genetic diversity of B. pseudomallei in Cambodia. The identified STs were closely associated with isolates from other Southeast Asian countries, particularly Thailand, Vietnam, and Malaysia. In conclusion, this study provided insight into the genetic diversity among B. pseudomallei clinical isolates in Cambodia and their close genetic association with Southeast Asian isolates. To further our understanding, a One Health approach, incorporating human, environmental (mainly soil), and animal compartments, is essential to decipher the epidemiology of B. pseudomallei in Cambodia.